Entrepreneurial Migration and Regional Opportunities in Developing Countries - Marthen L. Ndoen; Cees Gorter; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2000)
This paper aims to investigate the entrepreneurial migrants' preferences for a location for businessactivities in developing countries. In the modelling framework six socio-economic and six socio-cultural variables are used in this study to investigate the migrants' propensity to stay at aparticular region. The empirical research was carried out in East Nusa Tenggara, Indonesia. Itappears that the presence of a supporting informal network is the most critical factor that attractsand keeps the entrepreneurial migrants in a particular region. Socio-cultural variables likeexperience and education play a less significant role in the migrants' decision to stay in a givenregion.
Keywords: 330; Entrepreneurship-Ansatz; Entwicklungsländer; Migranten